Experiencing recent missionary evacuations: Traumatic stress and loss as social networks break down - Walters, Susan Gary (Missiology, 2022)
Although missionary evacuations have occurred since the beginning of missions, little research has explored modern missionary evacuations. In this qualitative study, the author analyzes the experiences of four missionaries who made unplanned departures from their Asian host country in 2018. Although each study participant had different demographic characteristics and their story was unique, common elements of the evacuation experience were shared: growing uneasiness, mounting stress, the decision to evacuate, a sudden exit, and waves of transition. The most traumatic aspect throughout the experience was the severe disruption of their relationships. Factors contributing to the breakdown of social networks included surveillance and scrutiny, searches and interrogations, contact tracing, the compromising of digital communication channels, and the final exit. The traumatic effects of the breakdown of social networks highlight the critical importance of relationships in the life and work of missionaries, particularly during crises. Understanding how evacuations are experienced enables the wider Church—which is preparing, sending out, and receiving missionaries back—to better care for its missionaries and contribute to their restoration and healing from trauma.